The comparison of extraction methods of ganjiang decoction based on fingerprint, quantitative analysis and pharmacodynamics - Yanyan Wei; Ning Jiang; Tuo Liu; Chang Liu; Wen Xiao; Likeng Liang; Tongming Li; Yang Yu (BMC, 2020)
Abstract Background Ulcerative colitis (UC) is a chronic nonspecific inflammatory disease of the colon and rectum with unknown etiology, and its symptoms include bloody diarrhea, abdominal pain, and hematochezia. Traditional Chinese medicine compound has a good therapeutic, multi-target effect on UC. Ganjiang decoction (GD), which is a traditional classic prescription in China, contains Zingiberis Rhizoma, Angelicae Sinensis Radix, Coptidis Rhizoma, Phellodendri Chinensis Cortex, Sanguisorbae Radix, Granati Pericarpium, and Asini Corii Colla and could be used to treat symptoms of UC. This study aimed to conduct a preliminary study before GD colon-targeted preparation, to explore the relationship between extraction method and efficacy of GD. Methods High-performance liquid chromatography (HPLC) was used for the fingerprinting of five preparation methods of GD. HPLC and gas chromatography were used to quantitatively analyze the important chemical components of GD and compare their differences. Mice with UC induced by dextran sulphate sodium salt received the extracts from the five preparation methods of GD via gavage. Disease activity index (DAI) score, colonic length, relative weight of spleen, pathological analysis results, inflammatory factors, therapeutic effect of the five preparation methods of GD, and their relationship with extraction process were compared. Results Cluster analysis revealed that the content of the components extracted by traditional extraction methods was significantly different from the other four methods. The third and fifth preparation methods extracted Coptidis Rhizoma and Phellodendri Chinensis Cortex with 50% ethanol to obtain more alkaloids. In the fourth and fifth methods, more volatile oils were detected by adding Zingiberis Rhizoma and Angelicae Sinensis Radix fine powder. According to DAI score, colonic length, relative weight of spleen, pathological analysis results, and inflammatory factors, the third method showed a good therapeutic effect, while the fifth method had the best therapeutic effect. Conclusions The results showed that the difference of the five extracts of GD in the efficacy of DSS-induced UC in mice was closely related to the extraction method. Our study improved the extraction process of GD and provided a foundation for the process of enteric-soluble preparations and a new idea for traditional Chinese medicine compound preparation.